Geographic Variation and Trends in Laryngeal Cancer Incidence in Iran: A Comprehensive Analysis - Farimah Asghari; Hamideh Rashidian; Fereshteh Lotfi; Fatemeh Mahdavi Sabet; Zahra Faraji; Kazem Zendehdel (Basic & Clinical Cancer Research)
Background and Aims: Laryngeal cancer poses a significant health challenge, particularly in Iran, where it exerts a substantial burden on the healthcare system. This study aimed to comprehensively analyze the geographic variation in laryngeal cancer incidence across Iran, estimate its burden in 2022, and project trends up to 2050.